Modeling behavior dynamics using computational psychometrics within virtual worlds - Cipresso, Pietro (Frontiers in Psychology, 2015)
In case of fire in a building, how will people behave in the crowd? The behavior of each individual affects the behavior of others and, conversely, each one behaves considering the crowd as a whole and the individual others. In this article, I propose a three-step method to explore a brand new way to study behavior dynamics. The first step relies on the creation of specific situations with standard techniques (such as mental imagery, text, video and audio) and an advanced technique (Virtual Reality) to manipulate experimental settings. The second step concerns the measurement of behavior in one, two or many individuals focusing on parameters extractions to provide information about the behavior dynamics. Finally, the third step, which uses the parameters collected and measured in the previous two steps in order to simulate possible scenarios to forecast through computational models, understand and explain behavior dynamics at the social level. An experimental study was also included to demonstrate the three-step method and a possible scenario.